2012
DOI: 10.1292/jvms.11-0220
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of <i>Escherichia coli</i> Isolated from Feces of Wild Cranes Migrating to Kagoshima, Japan

Abstract: ABSTRACT. Susceptibility to 13 antimicrobial agents was examined for 138 Escherichia coli isolates obtained from 192 fecal samples of wild cranes that migrated for wintering to the Izumi plain, Kagoshima prefecture in Japan. The numbers of isolates that were resistant to the antimicrobials used in this study are as follows: oxytetracycline (OTC), 22 isolates; minocycline, 7 isolates; ampicillin (ABPC), 4 isolates; nalidixic acid, 4 isolates; enrofloxacin, 2 isolates; kanamycin, one isolate. Multidrug resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
2
13
0
2
Order By: Relevance
“…A similar level of resistance was observed in previous reports in E. coli isolated from cranes birds (18.8%) and mallards (27%) [9,46].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…A similar level of resistance was observed in previous reports in E. coli isolated from cranes birds (18.8%) and mallards (27%) [9,46].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 90%
“…Moreover, the resistance genes of bacteria from wild birds may result in increased numbers of resistant bacteria in livestock and humans [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that antimicrobial-resistant bacteria are present in different wild animals that have not been exposed to antibiotics [6,7]. Moreover, the resistance genes of bacteria from wild birds may result in increased numbers of resistant bacteria in livestock and humans [8].…”
Section: Introductionmentioning
confidence: 99%
“…OTC-resistant strains have been detected in hooded cranes (Grus monacha) that inhabit cattle farms in the Kagoshima Prefecture, Japan. The greatest OTC MIC value in hooded cranes was 128 μg/ml (Kitadai, Obi, Yamashita, Murase, & Takase, 2012); in Okinawa rails, we detected a higher resistance to OTC (MIC ≥ 256 μg/ml). Oonaka, Furuhata, Kiuchi, Hara, and Fukuyama (2004) Although the use of ABPC in human therapy is quite rare (Terada, Miyake, & Urase, 2012), 16 t/year of bulk powder has been sold in Japan for use with domestic and pet animals (National Veterinary Assay Laboratory Ministry of Agriculture, Forestry, & Fisheries of Japan, 2012).…”
Section: Re Sults and Discussionmentioning
confidence: 56%
“…OTC‐resistant strains have been detected in hooded cranes ( Grus monacha ) that inhabit cattle farms in the Kagoshima Prefecture, Japan. The greatest OTC MIC value in hooded cranes was 128 μg/ml (Kitadai, Obi, Yamashita, Murase, & Takase, ); in Okinawa rails, we detected a higher resistance to OTC (MIC ≥ 256 μg/ml). Oonaka, Furuhata, Kiuchi, Hara, and Fukuyama () compared AMR bacterium MIC values in samples from the environment and of human clinical origin, and found higher MIC values in human clinical isolates.…”
Section: Resultsmentioning
confidence: 68%